Nuovi modi di condividere il sapere - Milazzo, Natalia; Carra, Luca; Bianchi, Massimo (Unimi Connect - Universo Terza Missione, 2023)
This second volume of the Unimi Connect - Universo Terza Missione series depicts a university that is opened up to society. The book provides a detailed account of 12 projects proving that knowledge can be a formidable engine of social innovation when it is shared with society. The section "Opening up to science and culture" offers an insight into five initiatives differing in themes and scopes but sharing a common denominator in their impact on society. The book explores the following topics: Botanical gardens' role in research advancement and knowledge dissemination; the University of Milan Orchestra's contribution to a thriving cultural environment; the establishment and consolidation of relations with China; the University's commitment to open access policies to foster knowledge sharing dynamics; the positive impact of studies on the toxicological safety of products on our daily life. The second section is entitled "Opening up to young people". Engagement in innovative knowledge dissemination activities conveys researchers' passion for science and proves that even the most complex ideas and concepts can be accessible in a fun, yet scientifically sound, manner. In this section, you might read about programs on stem cells and brain research engaging high school students, games designed to attract the generic public to the World of Dante and theater plays unvealing the charm of Physics. The book concludes with a focus on archaeological research, highlighting not only its contribution to new discoveries, but also its role in consolidating relations with territories, strenghtening local identities and advancing innovation. The last section "Apri all'Antico" takes the reader on a journey to the discovery of the magnificent archeological sites of Aswan in Egypt and Tarquinia and Poviglio in Italy.